Effects of flipped and conventional teaching approaches on performance and retention ability of students in advance financial accounting in Abubakar Tafawa Balewa Uuniversity Bauchi, Nigeria - Ibrahim, Adamu; Haruna, Jibril Alhaji (Penerbit Universiti Kebangsaan Malaysia, 2017)
The study investigated the effects of flipped and conventional classroom teaching approach on performance and retention ability of advance financial accounting students in Abubakar Tafawa Balewa University Bauchi, Nigeria. The study had three specific objectives and three null hypotheses. Quasi experimental design of pre-test, post-test I and post-test II was used for the study. The study used an intact class of 76 students that offered advance financial accounting in 2015/2016 academic session in the institution. Three instruments were used for data collection. The instruments were Advance financial accounting Achievement Test (AFAAT), Advance financial accounting Diagnostic Achievement Test I (AFADAT I) and Advance financial accounting Diagnostic Achievement Test II (AFADAT II). The validations of instruments were determined by board of examiners in department of vocation al and technology education in Abubakar Tafawa Balewa University, Bauchi. The reliability of the instruments was established using pilot study. The result of the pilot study gave reliability coefficient of 0.79. Data collected from the study were coded into Statistical Package of Social Sciences. The package was used to run t-test statistics for the test of the three null hypotheses at significance level of 0.05. The results shows improvement in the performance and retention ability of students when flipped teaching technique was adopted. It was recommended among others that financial accounting lecturers in Nigerian universities should adopt the use of flipped classroom approach in teaching students by providing students with pre-class materials and assignments prior their classroom activities.